Relapsing Sudden Hearing Loss Treated and Prevented with Principles of Persian Medicine: A Case Report - Somayyeh Khalilzadeh; Mahdi Alizadeh Vaghasloo (Tehran University of Medical Sciences, 2019)
WHO has declared sudden hearing loss (SHL) as the third cause of disability. The mechanism of SHL remains unknown. Considering numerous complications of related medication, we decided to use non-medical therapeutic modalities derived from Persian Medicine (PM). A middle-aged female patient had a history of multiple attacks of SHL, she disliked to get injection again and preferred a traditional treatment. Therefore, she was advised to take a simple protocol in order to make rheological changes in and evacuation of the probable stagnant phlegmatic matter as it was diagnosed from the given oral history. The hearing loss recovered 60% after the first attempt and up to 100% after the second round and has not yet relapsed in the recent two and a half years of follow up despite its recurrences in the year before the trial. In this patient, by using safe user-friendly methods without any medications, we tried to increase the blood circulation to the affected organ, in order to change the consistency of the stagnated waste material so that it could be disposed from the auditory nerves and also out from the body.